RECONFIGURING TECHNICAL AGROINDUSTRIAL EDUCATION IN RURAL CONTEXTS: STRUCTURAL CHALLENGES, TECHNOLOGICAL INNOVATION, AND THE HORIZON OF SUSTAINABILITY - Fredy Enrique Martinez Valencia; Edid Clara Rosero Riascos (LÍNEA IMAGINARIA, 2025)
This article offers a critical review of technical secondary education in agroindustrial fields within rural contexts, adopting a documentary and retrospective approach to examine the main advances, tensions, and structural challenges that shape its relationship with sustainable rural development, food security, and technological innovation. The analysis draws on national and international scholarly literature published between 2020 and 2024, as well as regulatory frameworks that guide rural education policies in Latin America. The findings reveal a persistent disconnect between technical education programs and the socio-productive dynamics of rural territories, manifested in inadequate curricula, insufficient teacher training, limited technological transfer, and a lack of integration of sustainability-oriented approaches. Agroindustrial technical education remains anchored in operational and standardized models that fail to respond to the complexity of rural realities or to foster transformative educational processes. In response, this study advocates for a reconfiguration of educational models based on principles of equity, pedagogical resilience, circular economy, responsible use of technology, and the inclusion of local knowledge systems. Technical education is framed as a strategic mechanism for enhancing productive autonomy, strengthening food sovereignty, and enabling territorial transformation grounded in social justice. The conclusions call for overcoming the functionalist view of agroindustrial education and repositioning it as a key driver of structural change through effective articulation between science, public policy, and community-based knowledge.